Exploring Similarities Between AI-Generated Writing and Students’ Writing in Producing Descriptive Text at Hamzanwadi University - Reswita, Firna; Nazri, M. Adib; Marzuki, M. Junaidi; Prasetyaningrum, Ari (PROJECT (Professional Journal of English Education), 2026)
This study explores the similarities between descriptive texts written by second-semester English education students at Hamzanwadi University and a text generated by ChatGPT in response to the same writing prompt. Using a qualitative descriptive method, seven student texts selected from fifteen submissions and one AI-generated text were analyzed with the IELTS Writing Band Descriptors, focusing on Task Response, Coherence and Cohesion, Lexical Resource, and Grammatical Range and Accuracy. The findings indicate that both texts shared similarities in addressing the task, maintaining coherence, using descriptive vocabulary, and applying varied sentence structures, although the AI-generated text demonstrated greater lexical variety and fewer grammatical errors. These results suggest that AI-generated writing can serve as a supplementary model for students in developing descriptive writing skills, while teacher guidance remains crucial to ensure critical and effective use of AI tools.